The Concept Of “Joy” In Modern English - Sharipova Muxlisa (Peerian Journals Publishing, 2024)
The article is devoted to study the concept “Joy” and ways of expressing versions of “Joy” in Modern English language
Keywords: concept; joy; lexico-semantic field; stylistic